Metabolic regulation of intestinal epithelial barrier during inflammation - Colgan, Sean P (Tissue Barriers, 2014)
The gastrointestinal mucosa has proven to be an interesting tissue for which to investigate disease-related metabolism. In this review, we outline some evidence that implicates metabolic signaling as important features of barrier in the healthy and disease. Studies from cultured cell systems, animal models and human patients have revealed that metabolites generated within the inflammatory microenvironment are central to barrier regulation. These studies have revealed a prominent role for hypoxia and hypoxia-inducible factor (HIF) at key steps in adenine nucleotide metabolism and within the creatine kinase pathway. Results from animal models of intestinal inflammation have demonstrated an almost uniformly beneficial influence of HIF stabilization on disease outcomes and barrier function. Studies underway to elucidate the contribution of immune responses will provide additional insight into how metabolic changes contribute to the complexity of the gastrointestinal tract and how such information might be harnessed for therapeutic benefit.